Response Analysis of Submerged Floating Tunnel Hit by Submarine Based on Smoothed-Particle Hydrodynamics - Gang Luo; Shaokang Pan; Yulong Zhang; Liang Chen (Shock and Vibration)
This paper presents the theoretical investigation on the damage of the submerged floating tunnel (SFT) under extreme loads. Water was modeled by smoothed-particle hydrodynamics (SPH). Anchor cables, SFT, and submarine were modeled by the finite element method (FEM). Penetrating phenomenon in the calculation process was achieved by the penalty function, and the fluid-solid coupling effect was also considered in the simulation. The process of a submarine striking on the SFT was studied based on the commercial software. The relationships between the energy of the water, submarine, and SFT were studied. The structural and human damages were evaluated using the kinematics and kinetic parameters of the SFT according to the relevant criterion. The results indicate that the SPH-FEM coupling method is suitable to investigate the impact of the SFT in the water. The initial kinetic energy of the submarine is mainly converted into kinetic energy of the water and internal energy of the tunnel. The kinematic parameters at the impact point reach a peak value. The kinematic parameters at the anchor cables reach the minimum value, so the anchor cables can inhibit the development of disaster significantly. The SPH-FEM coupling method can be helpful for collision and explosion analysis of the SFT.